A mathematical model for the stationary process of rolling of tubes on a continuous mill - Gulyayev, Yu. G. (Materiali in tehnologije, 2009)
A mathematical model has been developed for the calculation of process parameters in continuous lengthwise plugless tube rolling. Examples of concrete calculations of rolling parameters, their comparison with experimental data and the results obtained with the application of other calculation procedures are given.
Keywords: cevi; valjanje; matematični modeli